2013
DOI: 10.1088/1475-7516/2013/04/025
|View full text |Cite
|
Sign up to set email alerts
|

Attractor behaviour in ELKO cosmology

Abstract: We study the dynamics of ELKO in the context of accelerated phase of our universe. To avoid the fine tuning problem associated with the initial conditions, it is required that the dynamical equations lead to an early-time attractor. In the earlier works, it was shown that the dynamical equations containing ELKO fields do not lead to early-time stable fixed points. In this work, using redefinition of variables, we show that ELKO cosmology admits early-time stable fixed points. More interestingly, we show that E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 48 publications
3
53
0
Order By: Relevance
“…These correspond to slow and fast-roll inflation. The latter being unique to Elko [68]. For earlier contribution to Elko cosmology from this group we refer to the reader to references [69,70].…”
Section: Locality Structure Of the New Fieldmentioning
confidence: 98%
“…These correspond to slow and fast-roll inflation. The latter being unique to Elko [68]. For earlier contribution to Elko cosmology from this group we refer to the reader to references [69,70].…”
Section: Locality Structure Of the New Fieldmentioning
confidence: 98%
“…Since recent works [65][66][67][68] have not found stable points for such system for different dynamic variables and interactions terms, we are led to believe (without demonstration) that the system ELKO-DM does not allow stable points. Based on these results, we have supposed there to be an additional constraint to the dynamical system, namely that the potential of the ELKO field is related to a constant parameter δ; then we have analyzed the stability conditions for such a new system.…”
Section: Discussionmentioning
confidence: 89%
“…Such a search for adequate variables depends in general on the structure of the physical quantities involved, like the energy density, pressure and Friedmann constraints. In some recent works [65][66][67], different choices of variables for interacting systems concerning the ELKO field have shown that there are no stable points in order to explain the cosmic coincidence problem. In [68] a new method of analysis was proposed, based on a constant parameter that leads to stable points under some conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Elko spinor fields have been investigated in the last decade [8][9][10][11][12][13][14][15][16][17][18] and has been further applied to gravity, cosmology, and field theory. [8][9][10][11][12][13][14][15][16][17][18] We recall that its starting point, in Ref.…”
Section: Dark Mattermentioning
confidence: 99%